Characteristics and management of 1093 patients with clinical diagnosis of familial hypercholesterolemia in Greece: Data from the Hellenic Familial Hypercholesterolemia Registry (HELLAS-FH). (October 2018) - Rizos, Christos V.; Elisaf, Moses S.; Skoumas, Ioannis; Tziomalos, Kostantinos; Kotsis, Vasilios; Rallidis, Loukianos; Garoufi, Anastasia; Athyros, Vasilios G.; Skalidis, Emmanouil; Kolovou, Genovefa; Koutagiar, Iosif; Papagianni, Marianthi; et al.
Abstract: Background and aims: Although familial hypercholesterolemia (FH) is one of the most common genetic disorders, it remains largely underdiagnosed and undertreated. The Hellenic Atherosclerosis Society has established the Hellenic Familial Hypercholesterolemia (HELLAS-FH) Registry, part of the Familial Hypercholesterolemia Studies Collaboration (FHSC), to evaluate the characteristics and management of patients with FH in Greece. Methods: Patients with diagnosed FH were recruited by a network of sites throughout Greece. The prevalence of cardiovascular disease (CVD) risk factors, as well as management of FH, was recorded. Results: This interim analysis included 1093 patients (556 male; 950 adults). The median age of FH diagnosis was 42.2 years (interquartile range 27.2–53.0). A family history of CVD was present in 47.8%, while 21.1% of patients had a personal history of CVD. At diagnosis, low-density lipoprotein cholesterol (LDL-C) was 241 ± 76 mg/dL in adults and 229 ± 57 mg/dL in children. Overall, 63.1% of the patients were receiving hypolipidemic drug treatment, mainly statins, at inclusion in the registry. Mean LDL-C of patients receiving drug treatment was 154 ± 76 mg/dL in adults and 136 ± 47 mg/dL in children. The majority of treated patients (87.9%) did not achieve LDL-C targets. Conclusions: FH in Greece is characterized by a significant delay in diagnosis and a high prevalence of both family and personal history of established CVD. The vast majority of FH patients do not achieve LDL-C targets. Improved awareness and management of FH are definitely needed. Highlights: Familial hypercholesterolemia (FH) in Greece is diagnosed at a late age. FH patients have a high burden of personal and family history of premature CVD. FH patients are undertreated, with only a small percentage achieving LDL-C goals.